Cote d'Ivoire : Second Reviews under an Arrangement under the Extended Credit Facility and the Extended Arrangement under the Extended Fund Facility-Press Release; Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Cote d'Ivoire's Second Reviews Under An Arrangement Under the Extended Credit Facility (ECF) and the Extended Arrangement Under the Extended Fund Facility (EFF). Performance under the EFC/EFF-supported program was strong in the first half of 2017. All performance criteria and indicative targets for end-June 2017 were observed and all structural benchmarks were met. Sound policies implemented by the authorities in the context of the IMF-supported program have helped secure confidence of the international financial markets, which enabled a successful Eurobond issuance in June. The IMF staff supports the authorities' requests for completion of the second reviews of the program supported by the ECF and EFF arrangements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet